Pembentukan Karakter Toleransi Melalui Pembelajaran PAI Di SMA Maarif Sukorejo - Mohammad Subkhan Hidayatulloh; Ahmad Marzuki (AL-Ikhtiar : Jurnal Studi Islam, 2025)
Education, particularly Islamic Religious Education (PAI), plays a strategic role in shaping students' character, including the essential value of tolerance in a multicultural society. Character, as a moral foundation and a distinguishing factor for humans from other creatures, needs to be instilled early on through a structured and contextual approach in education. This study focuses on the formation of a tolerant character through Islamic Religious Education learning at SMA Maarif Sukorejo. The purpose of this study is to describe the strategies, approaches, and impacts of PAI learning in shaping a tolerant character within the school environment. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Primary data sources were obtained from PAI teachers and students, while secondary data came from relevant school documents. Data analysis was conducted using the Miles and Huberman approach, which includes data reduction, data presentation, and inductive conclusion drawing. The results show that PAI learning at SMA Maarif Sukorejo has been integrated with the values of tolerance through a contextual and habituation approach. Strategies such as habituation, role models, case discussions, and the use of flexible curricula such as the Merdeka Curriculum have proven effective in shaping students' character. The value of tolerance is instilled through fair treatment without discrimination and respect for differences. Islamic Religious Education (PAI) teachers serve as moral guides, and the school creates an inclusive, collaborative, and contextual learning ecosystem. Character education at this school demonstrates that Islamic Religious Education (PAI) learning can serve as a vehicle for transforming values, leading to a generation that is not only intellectually intelligent but also morally and socially mature. Abstrak Pendidikan, khususnya Pendidikan Agama Islam (PAI), memiliki peran strategis dalam membentuk karakter peserta didik, termasuk nilai toleransi yang esensial dalam masyarakat multikultural. Karakter sebagai fondasi moral dan pembeda manusia dari makhluk lainnya perlu ditanamkan sejak dini melalui pendekatan yang terstruktur dan kontekstual dalam dunia pendidikan. Penelitian ini difokuskan pada pembentukan karakter toleransi melalui pembelajaran Pendidikan Agama Islam di SMA Maarif Sukorejo.  Tujuan dari penelitian ini adalah untuk mendeskripsikan strategi, pendekatan, serta dampak pembelajaran PAI dalam membentuk karakter toleransi di lingkungan sekolah tersebut. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Sumber data primer diperoleh dari guru PAI dan siswa, sedangkan data sekunder berasal dari dokumen sekolah yang relevan. Analisis data dilakukan dengan pendekatan Miles dan Huberman, yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan secara induktif. Hasil penelitian menunjukkan bahwa pembelajaran PAI di SMA Maarif Sukorejo telah terintegrasi dengan nilai-nilai toleransi melalui pendekatan kontekstual dan habituasi. Strategi seperti pembiasaan, keteladanan, diskusi kasus, serta pemanfaatan kurikulum yang fleksibel seperti Kurikulum Merdeka, terbukti efektif dalam membentuk karakter siswa. Nilai toleransi ditanamkan melalui perlakuan adil tanpa diskriminasi serta penghargaan terhadap perbedaan. Guru PAI berperan sebagai pembimbing moral, dan sekolah menciptakan ekosistem pembelajaran yang inklusif, kolaboratif, serta kontekstual. Pendidikan karakter di sekolah ini menunjukkan bahwa pembelajaran PAI mampu menjadi sarana transformasi nilai menuju generasi yang tidak hanya cerdas intelektual, tetapi juga matang secara moral dan sosial